2012
DOI: 10.1111/j.1365-2613.2012.00813.x
|View full text |Cite
|
Sign up to set email alerts
|

Amitriptyline aggravates the fibrosis process in a rat model of infravesical obstruction

Abstract: Infravesical obstruction (IVO) secondary to benign prostatic hypertrophy can affect up to 50% of men over 50 years old and may cause serious and irreversible alterations throughout the urinary tract, especially in the bladder. Therapeutic approaches are currently limited. Amitriptyline has recently been described as an analgesic, anti-inflammatory and myorelaxant in some experimental models. The objective of this study was to investigate the effects of amitriptyline hydrochloride on the process of fibrosis in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 45 publications
2
4
0
Order By: Relevance
“…In general, antidepressants have been reported to induce profibrotic responses via lysophosphatidic acid signaling [12]. Our data are consistent with the ability of Amitrip to enhance TGF-β release and fibrosis [33]. The positive role of the TGF-β superfamily in mediating wound healing is well-documented and has been reviewed [34].…”
Section: Discussionsupporting
confidence: 84%
“…In general, antidepressants have been reported to induce profibrotic responses via lysophosphatidic acid signaling [12]. Our data are consistent with the ability of Amitrip to enhance TGF-β release and fibrosis [33]. The positive role of the TGF-β superfamily in mediating wound healing is well-documented and has been reviewed [34].…”
Section: Discussionsupporting
confidence: 84%
“…Histological examination of PDL in our study revealed apparently its increased thickness with areas of disorganization and degeneration. These results are in parallel with de Almeida Prado et al, (2012) who found that 20 mg/kg of Amitriptyline increased fibrosis in bladder of infravesical obstruction model in rats. They related this fibrosis to increased collagen deposition.…”
Section: Discussionsupporting
confidence: 88%
“…This could be explained by the relative short time span of the acute phase of inflammation. In the study by de Almeida Prado et al, a transition from neutrophil (polynuclear) to macrophage (mononuclear) infiltration in the bladder tissues of Wistar rats with BOO was observed between the first and the fourteenth day [ 25 ]. Similarly, Liang et al found macrophages infiltration in the bladder tissues of Sprague Dawley rats with BOO after 4 weeks [ 26 ].…”
Section: Discussionmentioning
confidence: 99%